IMPLEMENTASI PERMA NO 3 TAHUN 2022 TENTANG MEDIASI ELEKTRONIK TERHADAP PERKARA PERCERAIAN - Wafik Hajija Lonthor; Arianto (Institut Agama Islam Hasanuddin Pare, 2025)
Rapid advancements in information technology, especially with the issuance of Supreme Court Regulation (PERMA) Number 3 of 2022 concerning Electronic Mediation, have enabled mediation processes to be conducted online. This electronic mediation is expected to reduce case backlogs, accelerate dispute resolution, and provide easier access to justice for parties facing geographical constraints. However, the implementation of electronic mediation still faces various challenges, making it an interesting subject for further research, particularly in the context of divorce cases at the Religious Court of Kediri Regency. This study employs a field research approach with an empirical juridical perspective and a descriptive qualitative method. Primary data were obtained through in-depth interviews with mediators, the Head of the Planning, IT, and Reporting Sub-division, and staff at the Religious Court of Kediri Regency. Secondary data were gathered from literature, official documents, legal regulations (especially PERMA No. 3 of 2022 and PERMA No. 1 of 2016), scientific journals, and previous research findings. The research findings indicate that the implementation of electronic mediation at the Religious Court of Kediri Regency has proceeded in accordance with PERMA No. 3 of 2022, despite encountering several obstacles. Supporting factors include adequate facilities (mediation rooms, laptops, Zoom application, stable Wi-Fi), handling by professional staff and mediators, and effective communication between the parties. However, the main inhibiting factors are unstable internet connectivity at the parties' locations and a lack of feel to feel or emotional closeness between the mediator and the parties in online mediation. The benchmarks for successful mediation are not solely based on total reconciliation but also on partial agreements, such as agreements on child custody or alimony, which help resolve derivative issues of divorce peacefully.